Business concentration in the publishing sector: the case of Penguin Random House - Cruz Quintana, Fernando (Revista General de Información y Documentación, 2023)
This article presents an historical and contextual analysis of the concentration process that led to the creation of the transnational publishing house Penguin Random House. In this story, different stages are covered. The article theorizes about the importance of each moment’s technology and the economic processes have had for the formation of large consortia with interests in cultural production. Precisely, the work lists one of these groups: Bertelsmann, a German company with interests in different fields of culture and which has made Penguin Random House its publishing arm. Towards the end, the work emphasizes the Ibero-American scene and accounts for the way in which Penguin Random House has acquired Spanish-speaking labels and publishers.